2020
DOI: 10.21037/atm-20-4987
|View full text |Cite
|
Sign up to set email alerts
|

Micheliolide alleviates ankylosing spondylitis (AS) by suppressing the activation of the NLRP3 inflammasome and maintaining the balance of Th1/Th2 via regulating the NF-κB signaling pathway

Abstract: Background: Ankylosing spondylitis (AS) is a common form of inflammatory arthritis. Micheliolide (MCL), a sesquiterpene lactone, is reportedly involved in the alleviation of inflammatory response. This study aimed to investigate the mechanism of MCL in the treatment of AS.Methods: Mice were randomly divided into five groups: the sham group, the MCL (50 mg/kg) group, the AS model group, the AS + MCL (20 mg/kg) group, and the AS + MCL (50 mg/kg) group. After the addition of the inhibitor celastrol, mice were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The data gathered indicated that irradiation induces an inflammatory reaction accompanied by abundant production of pro-inflammatory cytokines, including IL-1β and IL-18. Interestingly, MCL alleviated radiation-induced intestinal damage and downregulated cytokine levels, consistent with previous reports ( Liu et al, 2019 ; Tian et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The data gathered indicated that irradiation induces an inflammatory reaction accompanied by abundant production of pro-inflammatory cytokines, including IL-1β and IL-18. Interestingly, MCL alleviated radiation-induced intestinal damage and downregulated cytokine levels, consistent with previous reports ( Liu et al, 2019 ; Tian et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Animal experiments indicated that Micheliolide, a sesquiterpene lactone involved in alleviating the inflammatory response, maintained the balance of Th1/Th2 by regulating NF-κB signaling (Tian, Yao & Chen, 2020). Th17 cells were shown to be involved in AS (Xueyi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 and Th2 chemokine levels decreased under etanercept, a TNF-α blocker, to improve the activity and functional capacity of AS patients ( Ergin et al, 2011 ; Wang et al, 2016 ; Zhang et al, 2018 ). Animal experiments indicated that Micheliolide, a sesquiterpene lactone involved in alleviating the inflammatory response, maintained the balance of Th1/Th2 by regulating NF-κB signaling ( Tian, Yao & Chen, 2020 ). Th17 cells were shown to be involved in AS ( Xueyi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…17 These signaling pathways and inflammatory factors are also involved in the etiological mechanisms of AS. [18][19][20] Selenium is a necessary trace element for the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Copper is a trace metal nutrient and excessive copper exposure can regulate the process of inflammation through various molecular and cellular signaling pathways, including the NF‐κB pathway, the Janus kinase‐signal transducer and activator of transcription pathway, and the nucleotide‐binding and oligomerization domain (NOD)‐like receptor protein 3 inflammasome 17 . These signaling pathways and inflammatory factors are also involved in the etiological mechanisms of AS 18–20 . Selenium is a necessary trace element for the human body.…”
Section: Introductionmentioning
confidence: 99%